Relationships Between Extension Workers' Competencies and Job Performance in Implementing the Good Agricultural Practices Programme in Malaysia - Tiraieyari, Neda (2009)
This study sought to determine extension workers' competencies that explain job performance in the case of the Good Agriculture Practices (GAP) Scheme at the Department of Agriculture, Malaysia. Specifically, the study determined extension workers' competency levels in clients' capacity development, SALM Standards, social skills and technology transfer process as independent variables. The study also determined the level of extension workers' job performance as a dependent variable. The study employed stratified random sampling technique. Samples are chosen using a proportional sample allocation. The sample consisted of 21 0 extension workers from the Department of Agriculture in four states of Malaysia, namely Perak, Negeri Sembilan, Kelantan and 10hor. Data were collected using a self administered questionnaire. The data were analyzed using descriptive statistics, Pearson correlation and multiple regression analysis. Results indicated that more than half of extension workers rated their level of job performance as high. A majority of respondents also rated their competency on leadership development, problem solving and decision making development, social skills, and technology transfer process skills as high. More than half of the respondents indicated high ratings for cultural and SALM program competencies. The finding supported the positive relationship between all competencies and job performance. However, only four competencies were significant in explaining job performance of extension workers. These are competencies on program evaluation, culture of clients, SALM program and social. This study is important as it contributes to the Interdependence Model of Extension by confirming competencies that extension workers need to have in both technical and human development. The findings would also assist policy makers and administrators in increasing the performance of extension workers. The competencies that have been identified in this study can be incorporated into both the pre-service and in-service training of extension workers.